Deception in Online Learning During the Pandemic of Covid-19 in Indonesia - Agustinus Rustanta; Desy Misnawati (Jurnal ILMU KOMUNIKASI, 2021)
Computer-mediated communication on distance learning brings various effects on thelecturers and the higher-education students. Distance learning has been performed on campusesin Indonesia since the pandemic of Covid-19. This research aims to describe the students’deception via computer-mediated communication. Interpersonal deception and computer-mediated communication theories are chosen to analyze this deception phenomenon. Data were collected through questionnaires and distributed to students in Jakarta as the red zone of the pandemic ofCovid-19. The findings show the students tended to manipulate information before they deliver it tothe audience and to hide their identity or presence during the virtual classroom.